Single Stage Transoral Laser Microsurgery for Early Glottic Cancer - Hamzany, Yaniv; Shoffel-Havakuk, Hagit; Devons-Sberro, Stav; Shteinberg, Shani; Yaniv, Dan; Mizrachi, Aviram (Frontiers in Oncology, 2018)
Objectives: The purpose of the study was to present the outcome of our management protocol of a single stage transoral laser microsurgery, with the intention of complete removal of a lesion, considered to be an early glottic cancer. Methods: Between January 2015 to February 2017 twenty-two patients meeting the inclusion criteria underwent endoscopic CO2 laser resection. Type of cordectomy corresponded to the pre- and intraoperative depth of invasion evaluation. Results: Four patients with severe dysplasia or carcinoma in situ underwent subepithelial (type I) and subligamental (type II) cordectomies in 3 and 1 patients respectively. Three patients with microinvasive carcinoma underwent subepithelial (type I) cordectomy. Fifteen patients with T1 glottic carcinoma underwent subepithelial (type I), subligamental (type II) and transmuscular (type III) cordectomies in 3, 6 and 6 patients respectively. An adequate extent of resection was selected in 21 out of 22 patients (95%). None of the patients was further treated by external beam radiation. At average follow-up of 21 months, none of the patients developed local recurrence Conclusion: In selected cases, a single stage transoral laser microsurgery for early glottic cancer allows a reliable histopathologic diagnosis and a high local control rate with favorable cost effectiveness. A careful pre- and intraoperative evaluation for selecting the appropriate cases for this management is required in order to avoid under- or overtreatment.